2011
DOI: 10.1093/cid/cir166
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pharmacokinetic-Pharmacodynamic Modeling and the Justification of a Novel Fusidic Acid Dosing Regimen: Raising Lazarus From the Dead

Abstract: Perhaps the most crucial step in the clinical development of an antimicrobial agent is the selection of a dosing regimen. Such decisions impact not only the success of a program but also the well being of individual patients, the emergence of resistance, and society as a whole. For fusidic acid, the selection of a dosing regimen for the treatment of patients with acute bacterial skin and skin-structure infection (ABSSSI) was based on the integration of knowledge gained from human population pharmacokinetic, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Our in vitro experiments and mechanism-based models do not include the effect of the immune system (50, 51) and thus mirror immunocompromised patients. Acknowledging the uncertainty arising from these potential limitations, mechanism-based Monte Carlo simulations can predict and rationally optimize bacterial killing and prevention of resistance for combination dosage regimens (19,31,38,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our in vitro experiments and mechanism-based models do not include the effect of the immune system (50, 51) and thus mirror immunocompromised patients. Acknowledging the uncertainty arising from these potential limitations, mechanism-based Monte Carlo simulations can predict and rationally optimize bacterial killing and prevention of resistance for combination dosage regimens (19,31,38,52).…”
Section: Discussionmentioning
confidence: 99%
“…The between-curve variability of the PD parameters was fixed to a coefficient of variation of 10% during the end of the estimation (28). Competing models were assessed by the objective function (Ϫ1ϫ log likelihood), plausibility of the parameter estimates, standard diagnostic plots, and visual predictive checks (37,38).…”
Section: Methodsmentioning
confidence: 99%
“…Although some bacterial counts at 119 and 167 h were slightly underpredicted by the model, this was attributed to experimental variability at relatively low bacterial counts. Since the model well described the bacterial counts and pharmacokinetic profiles over a large range of renal functions and meropenem concentrations, it may be useful for predicting the antibacterial effects of meropenem for other than the studied renal functions and ultimately to develop optimized dosing regimens (54,55). Although the simulation of plasma instead of tissue concentrations For the CL CR at 120 and ϳ10 ml/min, samples were collected as for the 285-ml/min CL CR , as well as at 29 and 31 h. For growth controls, the flow rates for the respective renal functions were maintained.…”
Section: Effect Of Meropenem Clearance On Antibacterial Effectsmentioning
confidence: 99%
“…Therefore, increasing the daily dose for colistin for a short duration seems a promising and clinically viable strategy to decrease the potential for nephrotoxicity while enhancing the antimicrobial killing activity. This strategy has been applied for other antimicrobials (42)(43)(44) and may be particularly promising for colistin, which can achieve rapid and concentration-dependent bactericidal activity (7). However, these findings should also be balanced with toxicodynamic evaluations of these new regimens, as it has been shown that the fAUC is the driver for nephrotoxicity for colistin (41,45).…”
Section: Discussionmentioning
confidence: 99%